Determinan Academic Fraud pada Mahasiswa dalam Mata Kuliah Akuntansi - Ardiansyah Ardiansyah (Universitas Prasetiya Mulya, 2021)
This study aimed to determine the effect of learning motivation, learning media, religiosity, rationalization, and academic pressure on academic fraud. Data was collected by distributing questionnaires to students of the Applied Business Administration (ABT) DIV Study Program, as many as 57 respondents. Due to the small number of samples, data processing was processed using the Partial Least Square (PLS) method. The findings in this study indicate that: (1) learning motivation has a negative and significant effect on academic fraud; (2) learning media has a negative and significant effect on academic fraud; (3) Religiosity has no effect on academic fraud; (4) Rationalization has a positive and significant effect on academic fraud; and (5) academic pressure has no effect on academic fraud. Empirically, this research reveals that religiosity and academic pressure are relative to everyone who can encourage them to do good or bad (academic fraud) depending on other more dominant factors. It suggests recommendations for further research to expand the number of respondents.